Kebijakan Luar Negeri Indonesia Menyangkut Ketidakikutsertaan Dalam Ratifikasi Konvensi UNESCO 1970 Untuk Memberantas Pencurian Dan Perdagangan Gelap Benda Cagar Budaya - Larosasari, Liliantoro Diyah; Pattipeilohy, Shary Charlotte Henriette (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
As a nation that rich in cultural heritage, thievery as well as illicit cultural propertyobject are still take place in Indonesia. Also called 'trafficking of cultural property', thiscriminal act categorized as a transnational crime. Later on UNESCO initiate aninternational regulation to oversee the cultural property movement amongst nations called1970 UNESCO Convention on the Means of Prohibiting and Preventing the Illicit Import,Export, and Transfer of Ownership of Cultural Property as a response towards numerouscases in this field that keeps occuring. Nevertheless, Indonesia has not willing to ratify theconvention as on of their foreign policy up to this moment. In order to study why Indonesiadid not ratify that international convention with annalyzing the data qualitatively thenexamine it using Rational Choice Theory by Hadiwinata and Glaser. Then based onresearch, it can be said that there are contrasts between UNESCO 1970 convention andIndonesia's law mechanism (2010 Law No. 11 about Cultural Object), the limited number ofhuman resources, and the slight interests of Indonesia with convention partying countries.